2012
DOI: 10.1038/npp.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa and Obesity are Associated with Opposite Brain Reward Response

Abstract: Anorexia nervosa (AN) is a severe psychiatric disorder associated with food avoidance and malnutrition. In this study, we wanted to test whether we would find brain reward alterations in AN, compared with individuals with normal or increased body weight. We studied 21 underweight, restricting-type AN (age M 22.5, SD 5.8 years), 19 obese (age M 27.1, SD 6.7 years), and 23 healthy control women (age M 24.8, SD 5.6 years), using blood oxygen level-dependent functional magnetic resonance brain imaging together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
257
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(279 citation statements)
references
References 68 publications
(84 reference statements)
17
257
2
3
Order By: Relevance
“…We found opposite functional brain response in women with anorexia nervosa compared with obese individuals, 8 suggesting opposite brain pathology. As previous studies have found increased intrinsic DMN activity in obese individuals, we hypothesized that DMN activity in women with anorexia nervosa would be reduced and thus opposite to that seen in obesity.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…We found opposite functional brain response in women with anorexia nervosa compared with obese individuals, 8 suggesting opposite brain pathology. As previous studies have found increased intrinsic DMN activity in obese individuals, we hypothesized that DMN activity in women with anorexia nervosa would be reduced and thus opposite to that seen in obesity.…”
Section: Introductionmentioning
confidence: 59%
“…1 While the neurobiologic al mechanisms underlying anorexia nervosa are not well understood, neuroimaging studies have found altered brain activation in brain regions contributing to reward and anxiety processing in individuals with anorexia nervosa. [2][3][4][5][6][7][8][9][10][11] Such alterations could be involved in the pathologic drive to eat in these individuals. 6,8 To gain a clearer understanding of neurobiological mechan isms involved in anorexia nervosa, it is important to under stand the functionality of the brain networks that underlie illness behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 were Coke consumers and 12 were nonsoda drinkers (Table 1), 2 qualified for neither consumer category and were only included in the subsample analysis. A Coke consumer was defined as consuming >5 Coca-Cola Classics ® (12floz/Coke) per week for more than the previous month.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In contrast, obese versus lean individuals show less striatal activity during palatable food intake (12)(13)(14), which may delay meal termination if individuals are seeking the previously experienced pleasure from food intake. In support, objectively measured food intake beyond needs correlated positively with activity in attention and gustatory regions when anticipating palatable food receipt (15), and striatal response during intake correlated negatively with frequency of consumption of foods similar to those in the scan (16,17).…”
Section: Introductionmentioning
confidence: 99%